Public Administration Reforms in Transition Countries: Albania and Romania Between the Webberian Model and the New Public Management - Denita CEPIKU; Cristina MITITELU (Transylvanian Review of Administrative Sciences, 2010)
A general trend is easily observable in the literature on public administration reforms in postcommunist countries and it consists in analyses of the degree of adoption and success of the New Public Management (NPM) model. Relevant implementation gaps for some levels as well as areas of reform, which cannot be ascribed to the NPM in these countries, are highlighted. The combination of these two features – also common, and not by accident, to other Continental European countries – may well be read as the adoption of a modernization framework different from the NPM, which some authors have come to recognize as the New Weberianism. Nonetheless, both models are not sufficiently developed and analyzed to provide a framework for evaluating country experiences. Therefore, the paper will firstly perform a systematic review of the literature on the context and cultural dependency of public management reforms, the debate on the NPM and the New Weberianism, with the aim of defining an analytical theoretical framework suitable for the analysis and comparison of country experiences; secondly, undertake an in-depth evaluation of public management reform trends in two countries – Albania and Romania – and contrast these with OECD countries’ experience. Public administrations of some European countries, including Albania and Romania, are not NPM “laggards” but have instead chosen to adopt a different modernization model: i.e. the New Weberianism. Implications for future research and policy-makers are drawn.